(untitled) (Journal of Paediatric Surgeons of Bangladesh, 2026)
Background: Overuse of antibiotics is worldwide concern. Although, Surgical site infection (SSI) is uncommon following clean surgeries and prophylactic antibiotics aren’t recommended for them, it is still used widely leading to super infection, higher cost, and antibiotic-resistant microorganisms in healthcare settings. The aim of this study was to compare the frequency of postoperative surgical site infection in inguinal herniotomy with or without peri-operative antibiotic in children. Methods: This quasi-experimental study was conducted in the Department of Pediatric Surgery at Chittagong Medical College Hospital from October, 2023 to March, 2025. A total of 176 patients were divided into two groups: Group A received peri-operative antibiotic Cephradine intravenously as single dose preoperatively, after induction and before incision. Then oral Cephradine 50 mg/kg/day orally in 4 divided doses for 7 days) (88 patients) and group B were not given any peri-operative antibiotic (88 patients). Patients were monitored on the 1st, 7th, and 30th post-operative days for SSI evaluation. Infections were assessed through serous discharge culture, and antibiotics were prescribed based on sensitivity results. Result: The mean age was 5.10 ± 2.88 years in Group A and 4.65 ± 3.05 years in Group B, (p>0.05).. 84.1% males in Group A and 83.0% in Group B (p>0.05). Right-sided hernia was more common in both groups (73.9% in Group A vs 67.0% in Group B, p>0.05). At the 1st and 3rd follow-ups, no cases of superficial surgical site infection (SSI) were reported in either group. At the 2nd follow-up, minimal signs of SSI were observed with no significant difference (p>0.05). Conclusion: Peri-operative antibiotic use in children undergoing inguinal herniotomy did not significantly influence the frequency of postoperative surgical site infections. Routine use of peri-operative antibiotics is unnecessary in uncomplicated pediatric inguinal herniotomy. Journal of Paediatric Surgeons of Bangladesh (2022) Vol. 13 (1 & 2): 25-29